The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1162/rest_a_01096
|View full text |Cite
|
Sign up to set email alerts
|

Crisis and the Trajectory of Science: Evidence from the 2014 Ebola Outbreak

Abstract: When crises such as disease outbreaks occur in low-income countries, the global response can inuence the output of researchers in the most affected locations. This paper investigates the impact of the 2014 West African Ebola epidemic on publication outcomes of endemic country scientists. Driven by collaborations with high-income country scientists in Ebola publications, endemic country scientists with relevant experience increase their publication output. However, the productivity of scientists without relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…Italy, UK, India, and Spain were slower to begin publishing but became more prolific through 2020, and particularly so in the final quarter. Fig 3 shows the rapid growth of monthly publications for selected countries, which also tracks with the trend in national COVID-19 cases; this finding is similar to one found in the 2014 West African Ebola epidemic [ 9 ].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Italy, UK, India, and Spain were slower to begin publishing but became more prolific through 2020, and particularly so in the final quarter. Fig 3 shows the rapid growth of monthly publications for selected countries, which also tracks with the trend in national COVID-19 cases; this finding is similar to one found in the 2014 West African Ebola epidemic [ 9 ].…”
Section: Resultssupporting
confidence: 73%
“…Prior research into collaboration around viral disease events found that, during the 2014 West African Ebola epidemic, collaboration grew between scientists from scientifically advanced nations and the most affected nations [ 9 ], suggesting that connections were made based upon disease location. Ebola outbreaks brought in researchers from scientifically advanced nations to work with local researchers on specific events.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific collaboration was expected to increase because of the urgency to generate effective vaccines, the high‐risk investment in anti‐pandemic products by individual nations, and resources constraints for research during pandemics (Gates, 2020; Lee et al, 2020). Focusing on the 2014 West African Ebola epidemic, Fry (2021) found increasing collaboration between the most affected countries and developed countries. The author attributed growing international collaboration to the need of sharing expertise, knowledge, data, and other resources between local scientists and foreign scientists.…”
Section: Introductionmentioning
confidence: 99%